Chinese Generation Xers’ Attitude toward Advertising:Evidence from Hong Kong and Shanghai Consumers - Ernest Cyril, de Run; Hiram, Ting; Fam, Kim-Shyan; Jozsa, Laszlo; Andrea, Solyom (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to examine Chinese Generation Xers’ attitude toward advertising and whether the ranking for ad likeability and dislikeability attributes are the same across Hong Kong and Shanghai. A telephone interview of 200 respondents in each city was conducted using a strategy of matched samples. The results show that the respondents from both cities find advertising ‘interesting and entertaining’,but ‘devious’. In terms of likeable attributes, they like ‘entertaining’, while ‘style’ is the most disliked attribute. The main difference between the two groups was found in attribute rating. The study concludes by offering several explanations for these variations.